The Efficient Approach in Peer-to-Peer Systems to Achieve High Efficiency - Lukman Santoso; Marcus Gunadi Wibawa; Muhamad Syarifudin; Priyadi; Titi Christiana (Journal of Management and Informatics, 2022)
Peer-to-peer systems nowadays are widely used because of the scalability and high reliability. File replication and consistency maintenance are widely used techniques to achieve high system performance. These techniques are connected to each other. The connection of these techniques is consistency maintenance is needed in file replication to keep the consistency between a file and the replicas. Traditional file replication and consistency maintenance methods need a high cost. The usage of IRM (Integrated file Replication and Consistency Maintenance inP2P systems) which will achieve high efficiency at a significantly lower cost can be used to solve this problem. IRM reduces redundant file replicas, consistency maintenance overhead, and unnecessary file updates.